Non-linear relationship between lipid accumulation products and risk of diabetes in Japanese adults - Fubing Zha; Miaoling Chen; Linlin Shan; Jingpu Zhao; Changchun Cao; Yulong Wang (Scientific Reports)
Abstract The lipid accumulation product (LAP) is a novel, sex-specific indicator of lipid accumulation. While previous studies have investigated the relationship between LAP and diabetes, they have not specifically addressed potential sex differences in this association. The present study explores the potential sex-specific differences in the relationship between LAP and diabetes mellitus (DM) risk in the Japanese population. From 2004 to 2015, a total of 15,263 Japanese individuals without DM underwent physical assessments at Murakami Memorial Hospital. The association between LAP and incident diabetes was analyzed using Cox proportional hazards regression models, incorporating cubic spline functions and smooth curve fitting to identify potential non-linear relationships. Subgroup and sensitivity analysis assessments were conducted to validate the robustness of our findings. After adjusting for covariates, a positive association between LAP and DM risk was observed in both females (HR: 1.02, 95% CI: 1.00-1.03, P = 0.0138) and males (HR: 1.01, 95% CI: 1.00-1.01, P = 0.0314). A non-linear association between LAP and incident DM was identified for both sexes. The inflection points for LAP were 16.58 for females and 11.11 for males. In females, the HR to the left and right of the inflection point were 1.09 (95% CI: 1.02–1.17) and 1.01 (95% CI: 1.00-1.03), respectively. In males, the HR to the left and right of the inflection point were 0.92 (95% CI: 0.86–0.98) and 1.01 (95% CI: 1.00-1.01), respectively. Sensitivity analysis indicated a stronger association between LAP and DM risk. Elevated baseline LAP levels were associated with an increased risk of incident DM, with the relationship exhibiting non-linear characteristics. These findings suggest that maintaining lower LAP levels may help mitigate the risk of developing diabetes.